Investigating the Potential of X-Ray-Based Cancer Treatment Equipment for the Sterile Insect Technique in Aedes aegypti Control Programs - Wang, Linmin; Liu, Tingting; Xiao, Liang; Zhang, Haiting; Wang, Cunchen; Zhang, Weixian; Zhang, Mao; Wang, Ying; Deng, Shengqun (Insects (Basel, Switzerland), 2024)
The sterile insect technique (SIT) stands as an eco-friendly approach for mosquito control, but it is impeded by the limited availability of γ-ray radiation source. This research sought to investigate a different radiation source—the Varian Clinac 23EX linear accelerator, which is frequently used for X-ray therapy in cancer treatment. Evaluation parameters including emergence rate, average survival time, induced sterility (IS), male mating competitiveness of irradiated males and fecundity (the number of eggs per female per batch), and the egg hatch rate of females mated with irradiated males were assessed to gauge the application potential of this cancer treatment equipment in the realm of the SIT. The results indicated that X-rays from radiation therapy equipment can effectively suppress the hatch rate of offspring mosquitoes without adversely affecting the emergence rate of irradiated males or the fecundity of females. In addition, at an X-ray dose of 60 Gy, the induced sterility in Ae. aegypti was comparable to the sterility induced by 40 Gy of γ-rays with both treatments resulting in 99.6% sterility. Interestingly, when a release ratio of 7:1 (irradiated males:unirradiated males) was used to competitively mate with females, the IS results resulted by 60 Gy X-rays and 40 Gy γ-rays were still at 70.3% and 73.7%, respectively. In conclusion, the results underscored the potential of the Varian Clinac 23EX linear accelerator as an X-ray source in SIT research.